Sexual HIV Transmission and Antiretroviral Therapy: A Prospective Cohort Study of Behavioral Risk Factors Among Men and Women Living with HIV/AIDS - Kalichman, Seth C. (Ann Behav Med, 2011)
BACKGROUND: Using antiretroviral therapies for HIV prevention relies on patient adherence and avoidance of co-occurring sexually transmitted infections. PURPOSE: The objective of this study is to simultaneously examine HIV treatment adherence and sexual risks for HIV transmission. METHODS: This study is a prospective cohort of 201 men and 55 women diagnosed with HIV/AIDS infection. RESULTS: A total of 32% men and 39% women engaged in unprotected intercourse with at least one HIV negative or unknown HIV status sex partner over 12 months. Nearly half (46%) of participants with HIV negative or unknown HIV status unprotected sex partners had detectable HIV viral load and were significantly more likely to have contracted a sexually transmitted infection since their HIV diagnosis. Individuals at higher risk for transmitting HIV were also less adherent to antiretroviral therapies. CONCLUSIONS: Programs that aim to use antiretroviral therapies for HIV prevention require careful attention to adherence, sexually transmitted co-infections, and substance use.